Antimicrobial Surveillance in Idiopathic Parkinsonism: Indication‐Specific Improvement in Hypokinesia Following Helicobacter pylori Eradication and Non‐Specific Effect of Antimicrobials for Other Indications in Worsening Rigidity. Issue 3 (22nd January 2013) - Dobbs, Sylvia M.; Charlett, André; John Dobbs, R.; Weller, Clive; Iguodala, Owens; Smee, Cori; Lawson, Andrew J.; Taylor, David; Bjarnason, Ingvar
<x xml:space="preserve">Abstract</x> Background Following Helicobacter pylori eradication in a placebo‐controlled trial, the hypokinesia of idiopathic parkinsonism improved but flexor rigidity worsened. Methods We surveyed the effect of all antimicrobial prescriptions in 66 patients with idiopathic parkinsonism over a median of 1.9 (interquartile range 0.4, 3.5) years. Initial Helicobacter screening was followed (where positive) by gastric biopsy. Serial lactulose hydrogen breath tests (364 tests) for small intestinal bacterial overgrowth monitored the need to encourage fluid intake and bulk/osmotic laxatives. We measured hypokinesia (401 assessments of mean stride length at free walking speed in 58 patients) and upper limb flexor rigidity (396 assessments in 49). Results Following successful H. pylori eradication (12 cases) but not failed (2), stride increased in entire group (including those receiving levodopa), core group (those receiving only longer‐t½ antiparkinsonian medication or untreated) and untreated (p = .001 each case). The effect was greater with less antiparkinsonian medication (19 (95% CI, 14, 25) cm/year in untreated). Flexor rigidity was unchanged. Following antimicrobials for other indications (75 courses), hypokinesia was unchanged. However, flexor rigidity increased cumulatively. It increased in core group only after a first course (by (10 (0, 20)%/year, p = .05)), but then in entire, core and untreated after a second course (18 (6, 31), 33 (19, 48) and 29 (12, 48)%/year respectively; p = .002, .001 and .001) and further still after a third (17 (2, 34), 23 (8, 41) and 38 (15, 65)%/year; p = .02, .003 and .001). Initially, 40/66 were lactulose hydrogen breath test positive. Odds for positivity fell with time (by 59 (46, 75)%/year, p = .001) and tended to be lower with Helicobacter positivity (28 (8, 104)%, p = .06), but were unrelated to other antimicrobial interventions. Conclusions Improved hypokinesia following antimicrobials appeared unique to Helicobacter eradication. Rigidity increased following successive antimicrobial exposures for other indications, despite diminishing lactulose hydrogen breath test positivity.